"Zurück zur Individualität!" die Rezeption moderner Religionsphilosophie im Hochland in der Weimarer Zeit - Peterson, Paul Silas 1979- (2020)
The monthly magazine Hochland was probably the most influential Catholic cultural periodical in Germany in the Weimar Period. According to Georg Cardinal von Kopp’s assessment in 1911, it was "unfortunately the most read periodical in all of the educated circles of Germany, Austria and German Switzerland". Moving beyond the simple rejection of modern culture in Germany, the journal tried to follow a new program of mediatory engagement, although it did continue to hold to traditional positions in many regards. In this article the reception of modern, Enlightenment-affirmative philosophy of religion in the journal is introduced with reference to reviews and essays from the later 1910s to the early 1930s. The journal’s treatment of a few critical subject areas is given close interpretive analysis, including the journal’s treatment of Gertrud Simmel’s Über das Religiöse, individually conceptualized forms of personalist moral theory, and the general shift to phenomenological discourses and the individual in the philosophy of religion. The fundamental rejections of these ideas and these schools of thought in reviews and essays, which are also found in the journal at this time (as in most all German language Catholic cultural journals of the period), are not addressed in this article. The article thus sheds light on an often-forgotten and relatively small minority phenomenon in German Catholic intellectual circles of the Weimar Period, namely the positive embrace of Enlightenment-oriented modern thought. By promoting these ideas at this time, this group made themselves highly vulnerable to disciplinary measures by the Catholic Church. (The journal was put on the Index in 1911.)
Keywords: Hochland; Phänomenologie; Neukantianismus; Ernst Robert Curtius; Karl Muth; Max Scheler; Gertrud Simmel